Assessment of commercial polymers with and without reactive groups using amino acid derivative reactivity assay based on both molar concentration approach and gravimetric approach. Issue 3 (4th October 2022) - Fujita, Masaharu; Nakashima, Natsumi; Wanibuchi, Sayaka; Yamamoto, Yusuke; Kojima, Hajime; Ono, Atsushi; Kasahara, Toshihiko
Abstract: The amino acid derivative reactivity assay (ADRA), an alternative method for testing skin sensitization, has been established based on the molar concentration approach. However, the additional development of gravimetric concentration and fluorescence detection methods has expanded its range of application to mixtures, which cannot be evaluated using the conventional testing method, the direct peptide reactivity assay (DPRA). Although polymers are generally treated as mixtures, there have been no reports of actual polymer evaluations using alternative methods owing to their insolubility. Therefore, in this study, we evaluated skin sensitization potential of polymers, which is difficult to predict, using ADRA. As polymers have molecular weights ranging from several thousand to more than several tens of thousand Daltons, they are unlikely to cause skin sensitization due to their extremely low penetration into the skin, according to the 500‐Da rule. However, if highly reactive functional groups remain at the ends or side chains of polymers, relatively low‐molecular‐weight polymer components may penetrate the skin to cause sensitization. Polymers can be roughly classified into three major types based on the features of their constituent monomers; we investigated the sensitization capacity of each type of polymer. Polymers with alert sensitization structures at their ends were classified as skin sensitizers, whereas those with no residual reactive groups were classified as nonsensitizers. Although polymers with a glycidyl group need to be evaluated carefully, we concluded that ADRA (0.5 mg/ml) is generally sufficient for polymer hazard assessment. Abstract : Regarding polymer involved reactive functional groups at the ends or side chains, relatively low‐molecular‐weight polymer components may penetrate the skin to cause sensitization. After classified into three major types, we investigated the sensitization capacity of each type of polymer using ADRA based on both molar concentration approach and gravimetric approach. As a result, polymers with alert sensitization structures at their ends were classified as skin sensitizers, whereas those with no residual reactive groups were classified as nonsensitizers.